1994
DOI: 10.1259/0007-1285-67-797-469
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum prostate specific antigen levels and bone scintigraphy in carcinoma prostate

Abstract: Serum prostate specific antigen (PSA) has been suggested as an accurate means of monitoring prostate cancer. An analysis of PSA levels and bone scan findings was carried out in a heterogeneous group of patients with a view to determine whether PSA can accurately predict bone metastases in carcinoma prostate. Of the 48 patients studied, all 10 untreated cases had elevated PSA levels, eight having bone metastases. In 29 cases on follow-up after treatment of the primary, 10 out of 11 cases with normal PSA had a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
2
10
0
2
Order By: Relevance
“…In a study of 48 patients of Ca. Prostate the mean serum PSA level was >109.9 ng/ml in the positive bone metastasis group and it was >54.7 ng/ml in the negative group as documented by Oommen et al [14]. The serum PSA level in the bone scan positive group was almost TWICE the serum PSA value in the negative bone scan group in this study too as shown by our reported values.…”
Section: Discussionsupporting
confidence: 81%
“…In a study of 48 patients of Ca. Prostate the mean serum PSA level was >109.9 ng/ml in the positive bone metastasis group and it was >54.7 ng/ml in the negative group as documented by Oommen et al [14]. The serum PSA level in the bone scan positive group was almost TWICE the serum PSA value in the negative bone scan group in this study too as shown by our reported values.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, some authors suggest the possibility of using PSA serum levels to predict possible scintigraphic findings (4,5,8,9,(11)(12)(13). Nevertheless, up to the moment, the literature presents disagreeing results in what concerns the cutting point to be adopted to predict the presence or absence of bone metastasis in prostate adenocarcinoma (1,10,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…No curso da terapia hormonal (15) , pacientes com níveis normais ou baixos de PSA podem ter evidência de progressão metastá-tica. Nestes casos, a cintilografia óssea é fundamental na detecção das metástases.…”
Section: A Cintilografia óSseaunclassified
“…Com o advento do antígeno prostático específico (PSA), surgiram novas abordagens e grandes discussões sobre o papel e importância da cintilografia óssea no estadiamento e acompanhamento dos pacientes com câncer de próstata (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) . Neste artigo foram revisados artigos da literatura no período de 1976 até 2003, para se chegar ao papel atual da cintilografia óssea na avaliação de tais pacientes e sua correlação com o PSA, seja no seu estadiamento, no seguimento sistemático ou no estudo de pacientes sintomáticos no seu curso evolutivo.…”
unclassified